Citizen-Sourced Sightings and Underwater Photography Reveal Novel Insights About Green Sea Turtle Distribution and Ecology in Southern California - Hanna, Megan E.; Chandler, Erin M.; Semmens, Brice X.; Eguchi, Tomoharu; Lemons, Garrett E.; Seminoff, Jeffrey A. (Frontiers in Marine Science, 2021)
East Pacific (EP) green turtles (Chelonia mydas) have undergone substantial population recovery over the last two decades owing to holistic protection at nesting beaches and foraging areas. At the northern end of their range in southern California United States, green turtles have been seen in more areas and in greater numbers since 2014 than before as a result. A resident population of green turtles has established near La Jolla Shores (LJS), a protected site with daily marine tourism (e.g., kayakers, snorkelers, divers). To study this local aggregation, innovative and non-invasive methods were required because the traditional capture-recapture methods were infeasible due to public relations sensitivities. Green turtle habituation to humans at this site has created a unique opportunity for citizen-based science using underwater photography to document turtles and their surroundings. We obtained 309 usable photographs of local green turtles from members of the dive/snorkel community in LJS. Photos were taken from April 2016 to June 2019. Images were processed in Hotspotter—a patterned species instance recognition software—to identify seven individuals, five of which were consistently photographed throughout that period. These images helped infer minimum residency duration (MRD), seasonal differences in algal coverage on the carapace, habitat association, behavioral patterns, and diet. Mean MRD was 424 days (SE = 131 days, calculated from entire population, n = 7), during which turtles were active in 82.8% of the photographs; the remainder of the photographs depicted foraging (14.9%) or resting behavior (2.3%). Green turtles were seen foraging in water temperatures as low as 15.8°C, the lowest recorded temperature for foraging green turtles documented in literature. Additional opportunistic observational platforms were used to look at trends of increasing green turtle abundance in southern California since 2015 that supported the arrival of a new aggregation of green turtles in LJS. Our use of citizen-sourced photographs confirms the presence of a resident aggregation of green turtles in LJS. Existence of green turtles and other protected species in highly populated areas provide excellent opportunities to educate beachgoers and seafarers about conservation of these species. This study also highlights the value of citizen-based science in areas where traditional research techniques are ill-suited.